Primary breast MALT lymphoma: a case report - Paffer, Pedro Toscano; Coimbra, Ana Luiza Serra; Souza, Gustavo Fonseca de Albuquerque; Costa, Lucas Nunes Viana da; Paffer, Matheus Toscano; Paffer Fillho, Silvio Hock de (Mastology, 2021)
A 42-year-old woman, with no history of autoimmune diseases or risk factors for cancer, sought a private medical clinic for undergoing breast imaging tests, noticing the presence of a solid nodule with indistinct margins — BI-RADS 4 — in the left breast. An ultrasound-guided core biopsy was performed and complemented by histopathological and immunohistochemical studies, confirming the diagnosis of primary small B-cell MALT lymphoma. After treatment with radiotherapy, the patient evolved with remission, maintaining annual follow-up with a specialist physician. The importance of routine screening for pathologies that affect the breasts is highlighted, aiming at their early diagnosis. In addition, radiotherapy has good prognostic results at the expense of surgical treatment.